PERHITUNGAN NILAI BETA DARI BEBERAPA SAHAM UNGGULAN DI INDONESIA DENGAN MENGGUNAKAN METODE GARCH - PUSPITAYANTI, NI KADEK; DHARMAWAN, KOMANG; N. KENCANA, I PUTU EKA (E-Jurnal Matematika; Vol 5 No 2 (2016)DO - 10.24843/MTK.2016.v05.i02.p123, 2016)
The objective of investment in the capital market is to acquire dividends and capital gain. The fact proves that the advantage of investation risky assets is uncertain . This is because of the difficulty in analyzing and predicting Return and stock losses due to factors that affect the movement of the stock price , such as economic factors , political , social , and security. The model can be used by investors in predicting stock returns expected that Generalized Autoregressive Conditional Heteroscedaticity (GARCH). In this study calculations beta value of some leading stocks in Indonesia by using Generalized Autoregressive Conditional Heteroscedaticity (GARCH) are presented . The data used this search is secondary data covering daily data sampled 5 shares of PT Unilever Indonesia Tbk , PT Indosat Tbk , PT Indofood Sukses Makmur Tbk , PT Telkom Indonesia Tbk , PT Holcim Indonesia Tbk. From the results described fifth beta value of these shares using the method GARCH beta greater than the market in the period from 23 September 2013 until 24 September 2014.
Keywords: Beta, Capital Gain, Dividen, GARCH, return